The Internet edge : social, legal, and technological challenges for a networked world - Stefik, Mark (MIT Press, 1999)
"Sometimes when we face change, we feel conflicting forces driving us forward and pulling us back. This place of tension and confusion can be called an "edge." The "Internet edge" is our collective struggle to change as the world becomes more connected. Turmoil at the Internet edge occurs around interacting social, legal, and technological realms. Examples include issues of online privacy, censorship, digital copyright, and untaxed business competition over the Net. Such issues reflect conflicts between values--local and global, individual and corporate, democratic and nondemocratic. This book is an eagle's eye view of the Internet edge. It is about the experiences of those who encountered similar issues as they built precursors to the Net such as videotext, teletext, and the Source. It is about the trends in technology that will make the Net of the next few years a very different experience from the desktop surfing of today. Finally, it is about how old myths of magic, power, and control can help us to understand our fascination with and fear of new technologies."--Publisher's description